Pengaruh Kelelahan dan Stres Kerja Terhadap Kinerja Individu Generasi Z - Abdullah Fahim (STIE Madani Balikpapan, 2025)
The dominance of gen Z in the workforce is a real cause for concern. According to 2022 Gallup survey data, 68% of gen Z workers feel stressed and around 34% feel exhausted. This research uses a quantitative approach. The sampling technique in this study used purposive sampling with the criteria of people born after 1997 to 2006. This study uses primary data obtained by distributing questionnaires directly to gen z in East Java. The data were analyzed using the Smart PLS 4 statistical tool. The results of this study explain if burnout has a negative and significant effect on individual performance and job stress has a negative and significant effect on individual performance.